The burden of physical activity-related ill health in the UK. - Allender, S; Foster, C; Scarborough, P; Rayner, M (2007)
BACKGROUND: Despite evidence that physical inactivity is a risk factor for a number of diseases, only a third of men and a quarter of women are meeting government targets for physical activity. This paper provides an estimate of the economic and health burden of disease related to physical inactivity in the UK. These estimates are examined in relation to current UK government policy on physical activity. METHODS: Information from the World Health Organisation global burden of disease project was used to calculate the mortality and morbidity costs of physical inactivity in the UK. Diseases attributable to physical inactivity included ischaemic heart disease, ischaemic stroke, breast cancer, colon/rectum cancer and diabetes mellitus. Population attributable fractions for physical inactivity for each disease were applied to the UK Health Service cost data to estimate the financial cost. RESULTS: Physical inactivity was directly responsible for 3% of disability adjusted life years lost in the UK in 2002. The estimated direct cost to the National Health Service is pound 1.06 billion. CONCLUSION: There is a considerable public health burden due to physical inactivity in the UK. Accurately establishing the financial cost of physical inactivity and other risk factors should be the first step in a developing national public health strategy.